认同建构与传统再造 ：新加坡妆艺大游行的性质与转变 (1973-1984) = Constructing identity and recreating tradition : the changing nature of Singapore Chingay Parade (1973-1984) - 陈慧婷 Tan, Hui Ting (2017)
由人民协会在农历新年期间举办的妆艺大游行，是新加坡最盛大的街头游行庆祝活动。举办妆艺大游行的最初目的，是为了抵偿因燃放鞭炮禁令的实施对农历新年气氛所造成的影响而所策划的。作为新加坡独立之后历史最悠久的文化艺术表演活动之一，本文将借由想象共同体与发明的传统两个理论，通过当时的新加坡华文报章，来分析1973年至1984年妆艺大游行主办机构的职能、参与表演团体的性质，以及每届表演节目的形式，以论证妆艺大游行是一项由新加坡政府所重新创造的“传统”，为的是服务政府促进多元文化的社会本质，维护社会当中的种族和谐。Organised by the People’s Association during the Chinese Lunar New Year, the Chingay Parade is Singapore’s largest street parade celebration. The initial aim oforganising Chingay Parade is to compensate the implementation of the Dangerous Fireworks Act in 1972, which forbids the discharge of firecrackers and therefore affects the atmosphere of Chinese New Year. As one of the oldest cultural and artistic performance event in post-independence Singapore, this thesis shall utilise the theories of Imagined Communities and Inventing Traditions to analyse the Chingay Parade from 1973 to 1984, focusing on the functions of the organisers, the nature of the participating performance groups and the form of every parade’s performances, for proving that the Chingay Parade is a ‘tradition’ invented by the Singapore government for promoting multiculturalism and to maintain racial harmony in the society.